A Review of Research on Sight Translation and Sight Translator Competences - Veresné Valentinyi, Klára (Acta Carolus Robertus, 2022)
Sight translation is a specific translation type which is receiving an increasing attention in translation research and education. An increasing number of translator and interpreter training higher educational institutions are teaching and using sight translation to develop translators’ and interpreters’ skills, and to test both translators’ and interpreters’ skills nationallly and internationally. As a consequence, sight translation is becoming a popular research topic and is being researched by higher educational students, the research results of which have been publisehd in some MA theses, true, sight translation is stull underresearched compared to other translation types. The aim of this paper is to give a review of recent research findings on sight translation, of which the presentation and research on sight translations competences are focused on in this article. In addition to literature review, two models of sight translation competencies are highlighted. The present article is a review article, which is not a research article but a presentation and summary of sight translation research results.